Determining the structural discontinuities in fractured carbonate reservoirs using FMS and VSP logs in the one of oil fields on West of Zagros - Moradi, Abdullah; Maleki, Bijan; Mafakheri, Nazir Anvar (Sulaimani Journal for Pure and Applied Sciences, 2016)
A study is made into the structural discontinuities in an oil field to the west of the Zagros mountain range, on the border between Iran and Iraq. Many oil reservoirs in the west of Iran and in the Kurdistan Region of Iraq are of fractured carbonate type. Faults and folds can change the structure of the reservoir. In such reservoirs, the study of the structural discontinuity leads to the discovery of complex geological structures. This complexity can impact on the discovery of a path to the reservoir. In one such oil field in western Zagros the reservoir was expected to be located at a particular depth but the new drilling well did not meet the reservoir. In this paper, Formation Micro Scanner (FMS) and Vertical Seismic Profile (VSP) have been used to determine the location of the structural discontinuities. Due to the low resolution of the VSP seismic data we find that it discovers the major faults and the formations borders, but will not be able to determine the small changes and complexity of the structure. Conversely, the FMS log(?) easily recognizes these microstructures. Therefore, with a combination of large-scale VSP data and small-scale FMS data we construct a 3D model. The results show that the well has been cut by five faults that dip to the north with the exception of a first fault to the south slope. To create the faults planes, AutoCAD software was also applied and the results are shown in this study.
Keywords: fracturecarbonate reservoirsFMS logVSP logwest of Zagros